Mildew-Omics: How Global Analyses Aid the Understanding of Life and Evolution of Powdery Mildews - Bindschedler, Laurence V.; Panstruga, Ralph; Spanu, Pietro D. (Frontiers in Plant Science, 2016)
The common powdery mildew plant diseases are caused by ascomycete fungi of the order Erysiphales. Their characteristic life style as obligate biotrophs renders functional analyses in these species challenging, mainly because of experimental constraints to genetic manipulation. Global large-scale (“-omics”) approaches are thus particularly valuable and insightful for the characterisation of the life and evolution of powdery mildews. Here we review the knowledge obtained so far from genomic, transcriptomic and proteomic studies in these fungi. We consider current limitations and challenges regarding these surveys and provide an outlook on desired future investigations on the basis of the various –omics technologies.